2010
DOI: 10.3389/fneur.2010.00142
|View full text |Cite
|
Sign up to set email alerts
|

GABAB Mediated Regulation of Sympathetic Preganglionic Neurons: Pre- and Postsynaptic Sites of Action

Abstract: Modulatory influences on sympathetic nervous system activity are diverse and far reaching, acting at select points in the complex pathways controlling sympathetic outflow to enable subtle changes or more global effects. Changes in the degree of sympathetic neuromodulation can have serious consequences on homeostatic variables such as heart rate, blood pressure and gut motility. At the level of the spinal cord, the sympathetic preganglionic neurons (SPNs) can be modulated by activation of presynaptic GABAB hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Also, an increase of prophylactic medication in subjects with migraine and depression, compared to migraine alone, has been described even though prophylactic treatment lines were not assessed [29]. Depression and migraine are bidirectionally associated, with both illnesses adding to the risk of developing the other [30]. Common neurological etiology is also shared between migraine, depression and sleep disorders [31], which in addition to reaction to severe stress and dorsopathies, were more frequent in patients with migraine compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Also, an increase of prophylactic medication in subjects with migraine and depression, compared to migraine alone, has been described even though prophylactic treatment lines were not assessed [29]. Depression and migraine are bidirectionally associated, with both illnesses adding to the risk of developing the other [30]. Common neurological etiology is also shared between migraine, depression and sleep disorders [31], which in addition to reaction to severe stress and dorsopathies, were more frequent in patients with migraine compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies indicated that highest prevalence of migraine occurs between ages 22 to 55 years old [21]. Berge LI et al represented a considerable decreased prevalence of migraine among older patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between migraine and obesity remains unclear, and results of various studies are inconsistent [21]. In two population-based studies, BMI was not correlated with the episodic migraine prevalence [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…The GABA B receptors also play a role in controlling SPN activity; these are present not only on the postsynaptic membrane but also on the presynaptic terminals arising from both descending and local GABAergic inputs to SPNs (Wang et al . ).…”
Section: Introductionmentioning
confidence: 97%